Clinical Evaluation of the Desensitizing Efficacy of a Paste Containing 8% Arginine and Calcium Carbonate - Thuy Anh Vu Pham; Thu Thi Anh Nguyen (Journal of Dental Problems and Solutions - Peertechz Publications, 2016)
Background: To evaluate the clinical efficacy of an in-office desensitizing paste containing 8% arginine and calcium carbonate relative to that of a commercially-available pumice prophylaxis paste when applied pre-procedurally to a dental scaling procedure (dental prophylaxis). Methods: This was a parallel group, randomized, double-blind, trial study conducted in 130 subjects who presented a tactile hypersensitivity score of 2 or 3 (Orchardson và Collins Tactile Sensitivity Scale) and an air blast hypersensitivity score of 2 or 3 (Schiff Cold Air Sensitivity Scale) and randomly assigned to one of two treatment groups. The two treatment groups were: (1) a Test paste, a desensitizing paste containing 8% arginine and calcium carbonate; and (2) a Control paste, Nupro pumice prophylaxis paste. Subjects had their assigned paste applied immediately before receiving dental scaling procedure. Record tactile and air blast hypersensitivity examinations score immediately after paste application and after the completion of the dental scaling procedure following the same methodology employed for the baseline hypersensitivity examinations. Results: At the final hypersensitivity examinations, the Test Paste and Control Paste groups were not statistically significant differences from baseline scores. Immediately following product application and after the completion of the dental scaling procedure, subjects assigned to the Test Paste group exhibited statistically significant improvements from baseline with respect to baselineadjusted mean air blast (38.9% and 37.4% respectively) and mean tactile hypersensitivity scores (40.2% and 42.4% respectively). At the same time points, subjects assigned to the Control Paste group exhibited statistically significant improvements from baseline with respect to baseline- adjusted mean air blast (16.0% and 17.8% respectively) and mean tactile hypersensitivity scores (14.6% and 16.4% respectively). Conclusion: The desensitizing paste containing 8% arginine and calcium carbonate provides reduction in dentin hypersensitivity immediately following product application and after the completion of the dental scaling procedure when applied as a single treatment before dental prophylaxis.